Development of Student Worksheet (LKPD) on Conventional Biotechnology Material for Grade X of Senior High School Through Bekasam Fermentation as Local Wisdom - Febrina, Hazirah; Mahadi, Imam; Syafi’i, Wan (FKIP - Universitas Riau, 2025)
Bekasam is a traditional fermented food made from fish, salt, and carbohydrate sources. The fish used in making bekasam are usually freshwater fish, one of the freshwater fish that can be used as the main ingredient in making bekasam is seluang fish (Rasbora argyrotaenia Blkr). This study aims to developing a student worksheet (LKPD) as alternative teaching materials for the conventional biotechnology in grade X senior high school, using findings from research on the effects of salt concentration and fermentation duration on bekasam made from seluang fish. This research is a quantitative study with a 3x3 factorial RAL experimental method with 3 replications so that a total of 27 treatments were obtained. The results showed that the best organoleptic and hedonic were in the P2T2 treatment (salt concentration of 20% and fermented for 10 days) namely a rather dull color (light brown), a distinctive bekasam aroma and a very strong aroma, the fish shriveled and soft, and the taste was very tasty. Furthermore, the development of LKPD was carried out using the ADDIE model, from the analysis, design, to development stages. From the validation results, it is known that the Student Worksheet (LKPD) for making bekasam seluang fish (Rasbora argyrotaenia Blkr) can be used in conventional biotechnology learning for class X SMA.